The Influence of Applied Educational Statistics Courses on the Competency of Students’ Quantitative Research - Vivin Devi Prahesti; Shaleh Shaleh (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2022)
Quantitative research competence is the main asset for students to be able to carry out quantitative research well and produce quality research results. One of the things that affect the quantitative research competence of a researcher is the mastery of applied statistics. This study aims to determine the effect of Applied Educational Statistics Courses on student competence in quantitative research. For this purpose, the researcher used a survey quantitative research method. The populations of this study were all students of the Madrasah Ibtidaiyah Teacher Education (PGMI) Master Program for the 2021-2022 Universitas Islam Negeri Sunan Kalijaga Yogyakarta who took the Applied Education Statistics course. The sample was taken using the proportional random sampling technique using the Slovin formula, to obtain a total sample of 12 students. Data were collected using a technical questionnaire that had proven its validity and reliability and analyzed by regression analysis. The results of this study indicate that the value of R2 (coefficient of determination) or R Square is 0.259 or 25.9%. This value can be interpreted that changes in student competence in quantitative research by changes in the value of the independent variable in statistics courses are 48, 54 % while 51,46 % is determined by changes in other factors. The calculated value for the Statistics course variable is 2, 203 with sig. 0.052 is smaller than 0.05. This shows that there is an influence of statistics courses on students' quantitative research competence and the factors that influence it.